Digital Turn for Sustainability: Unveiling the Role of Board Characteristics for Digital Transformation – CSR nexus - Muhammad Fuzail; Windijarto Windijarto; Rahmat Setiawan (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper examines the influence on digital transformation on corporate social responsibility (CSR). This study also investigates the moderating role of gender diversity while examining the abovementioned nexus. With 1161 companies at the period 2019 to 2023 that are listed in the Pakistan Stock Exchange, the paper addresses the influence that digital transformation has on the companies’ CSR performance and financial health. In this regard, it is proposed that company’s higher digitization level is positively associated with CSR activities. Where there is a diversity of boards it means that there will be better CSR strategies, which proves a positive relationship between board diversity and CSR performance. In conclusion, this research affirms that the corporate governance, sustainability, and financial performance are significantly affected by the digital transformation, providing the ground for the different authorities’ structures. This research is a reflection on the digital transformation as well as the board diversity and the corporate social responsibility on how the companies’ value and performance are generated.